Materials and process engineering aspects of warm deep rolling. (2017) - Oevermann, Torben; Saalfeld, Stephanie; Niendorf, Thomas; Scholtes, Berthold
For industrial applications efficient and short processes are essential, justifying the increased complexity of deep rolling treatments at elevated temperature. For this purpose, the direct integration of deep rolling manufacturing steps in heat treatment processes is a promising strategy. Combining inductive heat treatment with deep rolling leads to encouraging results concerning near surface material states as well as resulting fatigue strengths. Different process concepts are introduced and discussed. Characteristic results of near surface microstructures and residual stress states produced in this way for steels SAE 1045 and SAE 4140 are presented. In addition, the consequences of the material states and the microstructures on cyclic deformation behaviour and fatigue strength are outlined. The integrated system introduced allows the flexible application of appropriate process parameters, the analysis of their effects on the fatigue behaviour and the determination of optimised process conditions.